2010
DOI: 10.1080/10934520903468038
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of environmental estrogens in adipose tissue of breast cancer patients

Abstract: Although the estrogenic properties of numerous chloroorganic pesticides have been widely recognized, population studies do not give clear results indicating the link between the exposure to these compounds and breast cancer development. Because of the weak affinity of these pesticides to estrogen receptors, they probably act by affecting the expression of CYP genes encoding cytochromes P450 engaged in the metabolism of environmental as well as natural estrogens. To examine the possible correlation between envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…DDE concentrations and breast cancer risk. Localized delivery of p,p ´-DDE resulted in p,p ´-DDE concentrations in young and aged mice that are within the ranges detected in the human breast ( Falck et al 1992 ; Guttes et al 1998 ; Ociepa-Zawal et al 2010 ) and serum/plasma ( Cohn et al 2007 ; Eskenazi et al 2009 ; Snedeker 2001 ), as we predicted when selecting the 5-μg/pellet dose. Therefore, accelerated tumor development occurred with doses relevant to exposure in women.…”
Section: Discussionsupporting
confidence: 69%
“…DDE concentrations and breast cancer risk. Localized delivery of p,p ´-DDE resulted in p,p ´-DDE concentrations in young and aged mice that are within the ranges detected in the human breast ( Falck et al 1992 ; Guttes et al 1998 ; Ociepa-Zawal et al 2010 ) and serum/plasma ( Cohn et al 2007 ; Eskenazi et al 2009 ; Snedeker 2001 ), as we predicted when selecting the 5-μg/pellet dose. Therefore, accelerated tumor development occurred with doses relevant to exposure in women.…”
Section: Discussionsupporting
confidence: 69%
“…Of the 11,015 references retrieved by electronic search, 95 met eligibility criteria (Figure 1), of which 85 reported breast cancer incidence or prevalence outcomes [29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94,95,96…”
Section: Resultsmentioning
confidence: 99%
“…In our human study, results showed a relevant presence of DDT and its metabolites (Pestana et al, ). Furthermore, the compounds have been attributed carcinogenic effects, such as in breast cancer (Dich et al, ; Snedeker, ; Ociepa‐Zawal et al, ; Shakeel et al, ).…”
Section: Discussionmentioning
confidence: 99%